Indian physicians’ perception of clinical trials - Chandra, Phanish; Bhave, Radhika (International Journal of Clinical Trials, 2018)
The successful completion of clinical trials depends largely on the active participation of physicians. Tharyan, P (2007) has discussed at length, the opportunities, obligations, challenges, and solutions of conducting clinical trials in India (2-4). In this regard, an online survey was conducted on Docplexus to measure the physician awareness, understanding, and inclination towards the involvement in conducting clinical trials in India. Docplexus conducted a survey on 463 doctors specializing in Pharmacology/Clinical Pharmacology, General Medicine, Cardiology, Orthopedics, Neurology and Urology to understand their inclinations and concerns regarding clinical trials in India. A total of 53 doctors completed the survey. The data obtained from the survey was collected and analyzed to evaluate the parameters involved in inclination or aversion of physician participation and deduce perception.